Biotransformation of 2,6-diaminopurine nucleosides by immobilized Geobacillus stearothermophilus - de Benedetti, Eliana Celeste (2012)
An efficient and green bioprocess to obtain 2,6-diaminopurine nucleosides using thermophilic bacteria is herein reported. Geobacillus stearothermophilus CECT 43 showed a conversion rate of 90 and 83% at 2 h to obtain 2,6-diaminopurine-2′-deoxyriboside and 2,6-diaminopurine riboside, respectively. The selected biocatalyst was successfully stabilized in an agarose matrix and used to produce up to 23.4 g of 2,6-diaminopurine-2′-deoxyriboside in 240 h of process. These nucleoside analogues can be used as prodrug precursors or in antisense oligonucleotide synthesis.